(untitled) (KYAMC Journal, 2013)
Background: Non specific low back pain (NSLBP) has been identified as one of the commonest rheumatic disorders in prevalence surveys in Asia-Pacific. Objective: Development of a core questionnaire for identification of risk factors of NSLBP at community level. Methods: Following steps were followed: 1) item generation from literature survey, existing Nordic questionnaires and patient focus group discussions, 2) development of a preliminary APLARCOPCORD English questionnaire, 3) translation into target language, back translation and development of a synthetic target language version, 4) adaptation of the synthetic target language version through tests of comprehensibility, content validity test-retest reliability, and 5) finalization of the English questionnaire. Results: 45 items were generated. A preliminary English questionnaire was developed. Conclusion: The developed English questionnaire will serve as an efficient tool for identification of risk factors of NSLBP in Asia-Pacific communities. DOI: http://dx.doi.org/10.3329/kyamcj.v2i2.13263 KYAMC Journal Vol.2(2) January 2012, 187-192